Pengaruh Pemberian Pupuk Kasgot terhadap Pertumbuhan Tanaman Melada (Piper colubrinum Link.) - Utari, Marisa; Sulistyowati, Henny; Arifin, Nur (Fakultas Pertanian Universitas Tanjungpura, 2024)
Melada is a member of the Piperacea family, which is a perdu. Melada plants have properties that are resistant to the fungal attack Phytophthora capsici that causes basal stem rot disease; therefore, melada plants are used as rootstocks in pepper grafting to create pepper plants that are resistant to BPB disease. In this study, organic fertilizer was used as a nutrient enhancer in the soil; therefore, the type of organic fertilizer used was kasgot fertilizer (former maggot), which is expected to increase the nutrient content in the soil and have an influence on the growth of melada plants. The purpose of the study was to determine the effect of applying kasgot fertilizer on the growth of melada plants to increase their growth. This research will be conducted from August 16 to November 16, 2023. Research will be carried out at the Green House, Faculty of Agriculture, Tanjungpura University, Pontianak, West Kalimantan. This study uses a single-factor randomized group design (RAK) with factors in the form of applying Kasgot fertilizer. This study consists of 5 levels of treatment: K0 = Kasgot 0 g; K1 = Kasgot 20 g/1 kg alluvial soil; K2 = Kasgot 40 g/1 kg alluvial soil; K3 = Kasgot 60 g/1 kg alluvial soil; K4 = Kasgot 80 g/1 kg alluvial soil. The variables observed were an increase in shoot length, an increase in the number of leaves, root length, root volume, and plant biomass. The results of this study showed that the treatment of K3 with 60 grams of kasgot fertilizer/1 kg of soil had the best influence on the growth of melada plants.